Various Techniques of Fractal Image Compression - A Review (International Journal of Engineering and Computer Science, 2017)
Image compression is a method in which we can condense the space for storing images, video which will be helpful in transmission performance. There are many application which requires image compression such as multimedia, internet, remote sensing etc. This paper presents analysis of fractal image compression (FIC), fractal compression is a lossy compression methods for digital images, based on fractal. The method is appropriate for natural images and textures. FIC is an image coding technology based on the self-similarity of image structure and broadly used in image authentication, image denoising, image encryption etc. In this context, the review summaries the major FIC method spanning across different FIC technique.